Interesting Questions in Freakonomics - DiNardo, John (Journal of Economic Literature, 2007)
Freakonomics is more about “entertainment” than it is a serious attempt at popularization. Consequently, rather than conduct a comprehensive fact check, I use the book as a springboard for a broader inquiry into social science research and take issue with the book's surprising premise that “Economics is a science with excellent tools for gaining answers but a serious shortage of interesting questions.” Using examples from Freakonomics, I argue that some of the questions the book addresses are “uninteresting” because it is impossible to even imagine what a good answer would look like. I conclude with some thoughts about the role of economic theory in generating interesting questions and/or answers.